Preparation of iron catalysts supported in biomass arising from the coconut green shell for the falling of methylene blue (International Journal of Geoscience, Engineering and Technology, 2021)
The impact emitted by the elimination of contaminating residues led to an investigation of techniques and materials capable of solving this demand. Biomass is an abundant material, making it promising for the study of adsorption reactions of waste discharged into industrial effluents. Some methods increased the adsorption efficiency, such as Advanced Oxidative Processes (POAs). The availability and low cost of coconut shell becomes viable in the use of adsorption processes associated with POAs to decompose dyes in industrial waste. In this work, iron catalysts from the green coconut shell impregnated with this metal were prepared, and tests were carried out to study the decomposition of methylene blue. The harmful results that the Fenton process associated with adsorption was efficient in the degradation of the dye. All catalysts were active, with a sample containing 30% being the most effective, leading to 99.28% degradation after 30 minutes of reaction.